(untitled) (Research, Society and Development, 2022)
Objective: To evaluate the therapeutic effects and efficacy of cannabidiol as an alternative treatment to reduce the frequency of epileptic seizures, to improve the clinical picture of patients with epilepsy. METHODS: The present study is characterized as being an integrative literature review, with a qualitative approach in the period from 2015 to 2022.Results: research carried out through existing literature shows that cannabidiol (CBD) has great therapeutic potential, capable of significantly reducing epileptic seizures , and that its use did not cause serious side effects and toxic, and therefore its prolonged use proved to be safe, since the drugs patients did not show intolerance or dependence. The most common adverse effects were drowsiness, hyporexia, diarrhea, vomiting, behavioral changes and dizziness.